ANALISIS PENGGUNAAN APLIKASI E-TICKETING BIOSKOP (M-Tix) DENGAN DIMENSI PENERIMAAN TEKNOLOGI - Gusi Putu Lestara Permana; I Gusti Ngurah Darma Paramartha; Ida Ayu Winda Juniari (Jurnal Widya Akuntansi dan Keuangan, 2020)
The aim of this research was analyze factors that user accept e-ticketing software called m-tix using contruct from Technology Acceptance Model (TAM). Data were collected using questionnaire. The sample in this study were 75 respondents,and respondents determine with purposive sampling method. The results of this study was 1) percieved ease of use has a positive and significant effect on the use of m-tix. 2) percieved usefulness has a positive and significant effect on the use of m-tix. 3) trust has a positive and significant effect on the use of use of m-tix. 4) Self-efficacy has a positive and significant effect on the use of use of m-tix.